A Quantitative Approach to Production Planning and Inventory Control (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The significance of production planning and inventory control in enhancing efficiency in supply chain systems is tremendous in today's business environment. This study aims to provide a quantitative framework for the production planning and inventory control through mathematical modelling techniques. The goal of this proposed model is to optimize the production rate, size of inventory and how an inventory is replenished in order to minimise total cost (production cost, inventory cost, Setup cost, Shortage cost). The assumptions considered for this model are realistic in nature such as Demand Variations, Finite Production Rate, Backorder etc. to provide optimal production planning and inventory control across different types of industries. There is also an analytical optimisation technique used to optimise the various production planning and inventory control elements in this study which will provide an optimal cost minimising solution. The results of the study indicate that production planning and inventory control combined with the proposed model provide higher efficiency in minimising total costs than separate decision making approaches.”